Relevansi Ketentuan Kompilasi Hukum Islam Tentang Masa Berkabung Perspektif Mubadalah - Hud Leo Maki (Istinbath : Jurnal Hukum, 2021)
Ihdad is a period of mourning performed by the wife and husband, this is confirmed in KHI article 170 CHAPTER XIX about the period of mourning. However, in the article some words have the potential to cause problems, where the text in article 170 paragraph (1) greets women while not for men. The four words are wajib, iddah time, mourning, and slander. While the men in article 170 paragraph (2) are greeted with the word propriety. The perception raised by the article is the emergence of gender injustice in the form of stereotypes for women as a source of chaos. This study aims to find out how mubadalah reads the vision of ihdad reciprocity in KHI and mubadalah strategy in creating ihdad reciprocity for men and women. This research is a qualitative research using a content analysis approach, namely by dismantling KHI as an authoritative text with a trilogy of mubadalah (mabadi ', qawa'id, and juz'i). Meanwhile, to reveal the meaning of propriety in article 170 paragraph (2), the theory of ‘urf is used. The findings of the study are that in the perspective of mubadalah implicitly the text in article 170 already greets men and women. The application of the strategy of mubadalah in ihdad must pay attention to the traditions of the community. The contribution of this research is to increase the wealth of knowledge about the understanding of ihdad in KHI which has a vision of mubadalah as well as provide a strategy of mubadalah in realizing the reciprocity of ihdad so that it can be applied in society with a social and legal approach.